Critical realist case studies of foreign subsidiary development - Morais, Ricardo (2015)
In this methodological paper, I explore the potential of critical realist case studies for research on foreign subsidiary development. For that purpose, I begin with a review of the ontological, epistemological, and methodological assumptions of critical realism. Ontologically, reality is assumed to be stratified and emergent; epistemologically, knowledge is assumed to be transitive, but objective; and methodologically, research is expected to be highly contextual. In addition, I review the implications of such assumptions for causation, explanation, and generalization. In particular, causation is regarded as the manifestation of mechanisms rather than variables; explanation is based on retroduction rather than induction or deduction; and generalization is assumed to be transfactual rather than analytical or statistical. Critical realist case studies can thus be distinguished from other types of case studies for their emphasis on contextual explanation. In order to illustrate the potential for such case studies in international business research, I conclude with an application to foreign subsidiary development.